Systematic study of truffles in the genus Ruhlandiella, with the description of two new species from Patagonia. (4th May 2019) - Kraisitudomsook, Nattapol; Healy, Rosanne A.; Mujic, Alija B.; Pfister, Donald H.; Nouhra, Eduardo R.; Smith, Matthew E.
ABSTRACT: Ruhlandiella is a genus of exothecial, ectomycorrhizal fungi in the order Pezizales. Ascomata of exothecial fungi typically lack a peridium and are covered with a hymenial layer instead. Ruhlandiella species have nonoperculate asci and highly ornamented ascospores. The genus was first described by Hennings in 1903 to include the single species, R. berolinensis . Since then, mycologists have uncovered Ruhlandiella species in many locations around the globe, including Australia, Spain, Italy, and the USA. Currently, there are four recognized species: R. berolinensis, R. peregrina, R. reticulata, and R. truncata . All were found near Eucalyptus or Melaleuca trees of Australasian origin. Recently, we discovered two new species of Ruhlandiella in Nothofagaceae forests in South America. They regularly form mitotic spore mats directly on soil in the forests of Patagonia. Here, we formally describe these new species and construct the phylogeny of Ruhlandiella and related genera using a multilocus phylogenetic analysis. We also revise the taxonomy of Ruhlandiella and provide an identification key to accepted species of Ruhlandiella .